ANALISIS PENGARUH MOTIVASI TERHADAP KINERJA PADA KARYAWAN PT. BANK ACEH CABANG KUTACANE ACEH TENGGARA - Rahmat Arfan; Ardihirmansyah Ardihirmansyah (Faculty of Economics and Business, Universitas Malikussaleh, 2017)
The purpose of this journal is for determine relationship between motivations andjob performance staff at Bank Aceh branch Aceh Tenggara. The model of structurewas conducted in this analysis based on theory and research has been done relatedto motivation and job performance. The theory use in variable motivation is Theoryof Maslow and for variable job performance use element that has been conduct byMathis and Jackson. Analysis in this paper use three step there is reduction, presentation of data and conclution or verification. From this paper founded both of variable is influence each other, but there had dominant step in variable motivation there is appreciation, physiology and actualization, then for dominant step at performancevariable is quantity of job, quality of job and accuracy of time.